Long-term evidence of neonatal anaesthesia neurotoxicity linked to behavioural phenotypes in monkeys: where do we go from here?. (September 2021) - Raper, Jessica; Simon, Harold K.; Kamat, Pradip P.
Summary: Whether anaesthesia exposure early in life leads to brain damage with long-lasting structural and behavioural consequences in primates has not been conclusively determined. A study in the British Journal of Anaesthesia by Neudecker and colleagues found that 2 yr after early anaesthesia exposure, monkeys exhibited signs of chronic astrogliosis which correlate with behavioural deficits. Given the increasing frequency of exposure to anaesthetics in infancy in humans, clinical trials are greatly needed to understand how sedative/anaesthetic agents may be impacting brain and behaviour development.